Anti‐angiogenic activity of PSA‐derived peptides. Issue 12 (11th May 2015) - Chadha, Kailash C.; Nair, Bindukumar; Godoy, Alejandro; Rajnarayanan, Rajendram; Nabi, Erik; Zhou, Rita; Patel, Neel R.; Aalinkeel, Ravikumar; Schwartz, Stanley A.; Smith, Gary J.
<x xml:space="preserve">Abstract</x> BACKGROUND PSA is a biomarker for diagnosis and management of prostate cancer. PSA is known to have anti‐tumorigenic activities, however, the physiological role of PSA in prostate tumor progression is not well understood. METHODS Five candidate peptides identified based upon computer modeling of the PSA crystal structure and hydrophobicity were synthesized at >95% purity. The peptides in a linear form, and a constrained form forced by a di‐sulfide bond joining the two ends of the peptide, were investigated for anti‐angiogenic activity in HUVEC. RESULTS None of the five PSA‐mimetic peptides exhibited PSA‐like serine protease activity. Two of the peptides demonstrated significant anti‐angiogenic activity in HUVEC based on (i) inhibition of cell migration and invasion; (ii) inhibition of tube formation in Matrigel; (iii) anti‐angiogenic activity in a sprouting assay; and (iv) altered expression of pro‐ and anti‐angiogenic growth factors. Constrained PSA‐mimetic peptides had greater anti‐angiogenic activity than the corresponding linearized form. Complexing of PSA with ACT eliminated PSA enzymatic activity and reduced anti‐angiogenic activity. In contrast, ACT had no effect on the anti‐angiogenic effects of the linear or constrained PSA‐mimetic peptides. Modeling of the ACT‐PSA complex demonstrated ACT sterically blocks the anti‐angiogenic activity of the two bioactive peptides. CONCLUSIONS The interaction of a hydrophilic domain on the surface of the PSA molecule with a target on the cell membrane of prostate endothelial and epithelial cells was responsible for the anti‐angiogenic or anti‐tumorigenic activity of PSA: enzymatic activity was not associated with anti‐angiogenic effects. Furthermore, since PSA and ACT are both expressed within the human prostate tissue microenvironment, the balance of their expression may represent a mechanism for endogenous regulation of tissue angiogenesis. Prostate 75:1285–1299, 2015. © 2015 Wiley Periodicals, Inc.